2019
DOI: 10.1021/acs.jafc.9b05968
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identity of Galactooligosaccharide Molecules Selectively Utilized by Single Cultures of Probiotic Bacterial Strains

Abstract: Various β-galactosidase enzymes catalyze the trans-glycosylation reaction with lactose. The resulting galactooligosaccharide (GOS) mixtures are widely used in infant nutrition to stimulate growth of beneficial gut bacteria. GOS consists mainly of compounds with a degree of polymerization (DP) varying from 2–8 and with diverse glycosidic linkages. In recent years, we have elucidated in detail the composition of several commercial GOS mixtures in terms of DP and the structural identity of the individual compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…There is no correlation between the source of isolation of these strains and their capacity to utilize GOS, as both phenotypes harbor strains derived from human origin, fermented food or plant material (Table 1 ), confirming that the nomadic lifestyle of L. plantarum has consequences for the prediction of a strain’s genotype and corresponding phenotype based on the reported niche of isolation 17 . The distinction between the utilization of GOS-derived disaccharides and HDP-GOS constituents has also been reported for a panel of lactic acid bacteria strains of various species, showing that L. acidophilus W37 could utilize HDP-GOS, whereas L. salivarius W57 , L. paracasei W20 , L. casei W56, as well as Pediococcus acidilactici W143 and Enterococcus faecium W54 utilized only the disaccharide fraction of GOS 43 . Intriguingly, these observations are comparable to the “A” and “B” phenotype distinction observed for L. plantarum , illustrating that screening for prebiotic utilization should be performed at strain level, especially for species with high genetic and phenotypic diversity like L. plantarum .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There is no correlation between the source of isolation of these strains and their capacity to utilize GOS, as both phenotypes harbor strains derived from human origin, fermented food or plant material (Table 1 ), confirming that the nomadic lifestyle of L. plantarum has consequences for the prediction of a strain’s genotype and corresponding phenotype based on the reported niche of isolation 17 . The distinction between the utilization of GOS-derived disaccharides and HDP-GOS constituents has also been reported for a panel of lactic acid bacteria strains of various species, showing that L. acidophilus W37 could utilize HDP-GOS, whereas L. salivarius W57 , L. paracasei W20 , L. casei W56, as well as Pediococcus acidilactici W143 and Enterococcus faecium W54 utilized only the disaccharide fraction of GOS 43 . Intriguingly, these observations are comparable to the “A” and “B” phenotype distinction observed for L. plantarum , illustrating that screening for prebiotic utilization should be performed at strain level, especially for species with high genetic and phenotypic diversity like L. plantarum .…”
Section: Discussionmentioning
confidence: 68%
“…Our study also exemplifies that much more pronounced differences in growth, and more selective and strain-specific growth stimulation may be achieved by further purification of HDP-GOS constituents, specifically those of DP3-4 since import of higher DP GOS appears to be restricted in L. plantarum . Moreover, detailed chemical characterization of the constituents of GOS 5 , 43 may further enhance their selective application for stimulatory of growth and or activity of specific (intestinal) bacteria dependent on the substrate-specificities of their import and hydrolysis machinery. The approach taken in this study would be suitable to explore such future applications of specific fractions of GOS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study examining the metabolic capabilities of probiotic strains of bifidobacteria and lactic acid bacteria has revealed the superiority of HRB strains to assimilate galactooligosaccharide (GOS), a group of prebiotic compounds that are widely used in infant nutrition to stimulate growth of beneficial gut bacteria (Böger et al . 2019 ). HRB strains tested ( B. adolescentis DSM 20 083, B. breve DSM 20 091, B. bifidum DSM 20 456, B. longum subsp.…”
Section: Physiological Functions Of Human-residential Bifidobacteria mentioning
confidence: 99%
“…infantis (Böger et al . 2019 ). This study suggests that HRB strains particularly B. breve and B. longum subsp.…”
Section: Physiological Functions Of Human-residential Bifidobacteria mentioning
confidence: 99%
“…34 At the point of maximum GOS concentration, the most abundant GOS corresponded to 3'galactosyl-lactose (17. recently reported that most probiotic strains of gut bacteria exhibited a preference for DP2 galactooligosaccharides. 53 Fig. 6 represents the profile of GOS concentration as a function of lactose conversion.…”
Section: Progress Of Gos Formationmentioning
confidence: 99%